Secret hand gestures in paintings - Lazzeri, Davide; Nicoli, Fabio; Zhang, Yixin (Acta Biomedica Atenei Parmensis, 2019)
During the Renaissance period, hands were as important a focus of attention as the face was, because they were the only other visible area of the body. Hence, representation of the position of the hands became a decorative element that was almost as important as the face. Thus, given its high visibility, hand gestures in portraits and paintings have been one of the most effective ways of conveying secrets, codes and messages. From the historical and religious perspective, hand signs in visual art may provide clues about the underlying iconographical symbols. This paper will examine the eventual hidden meanings behind a peculiar hand gesture that has been widely used by several painters. (www.actabiomedica.it)